Ethnobotanical Study and Phytochemical Screening of Medicinal Plants Used by Local People in Belangian Village, South Kalimantan - Sutomo Sutomo; Vita Vitriana Awaliyah; Arnida Arnida (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The local people of Belangian Village are people of the Banjar ethnic group who utilize plants in the surrounding environment for medicinal purposes. This study aims to determine the number of plants, parts of plants that can be used, methods of application, methods of preparation, and phytochemical screening of plants with medicinal properties in Belangian Village. This study employed the descriptive-explorative method. The technique used for data collection was an interview with a semi-structured questionnaire. Respondents of this study were “Pananamba” who were selected by using the Purposive sampling technique. Phytochemical screening was carried out on plants with no previously known scientific names and which had never been tested before. The results showed 17 families and 31 species of plants with medicinal properties. Empirically, the plants were used as medicines for cough, bloody urine, diabetes, cancer, sprue, ulcer, hypertension, skin diseases, nausea, diarrhea, coronary heart disease, sinusitis, kidney stones, cleansing kidneys, menstrual pain, itchy eyes, paralysis, bone pain, increasing stamina, antibiotic, reducing body odor, wounds, bleeding, worm diseases, increasing appetite, boosting the immune system, and yellow fever. The most frequently used part of the plants were the leaves (45%), the most widely used method of preparation was boiling (52%), the most commonly used method of application was by drinking (81%). Phytochemical screening was conducted on three plants: Asam daun, Lukun, and Ulur-ulur. The results of phytochemical screening revealed the presence of quinones, saponins, and terpenoids in Asam daun, saponins in Lukun, and terpenoids in Ulur-ulur.